Meteorite reconnaissance in Saudi Arabia. (1st July 2018) - Hofmann, Beda A.; Gnos, Edwin; Jull, A. J. Timothy; Szidat, Sönke; Majoub, Ayman; Al Wagdani, Khalid; Habibullah, Siddiq N.; Halawani, Mohammed; Hakeem, Mohammed; Al Shanti, Mahmoud; Al Solami, Abdulaziz
Abstract: Meteorite searches in Saudi Arabia between 2008 and 2014 yielded 46 meteorites from the Yabrin area (23°N 49°E), 35 meteorites from the Rub' al‐Khali sand desert (19°–20°N, 48°–51°E), and 1 meteorite from Al Haddar. No meteorites were found near Hafar al Batin (29°N 45°E). The 82 new meteorites represent 57 falls comprising 43 ordinary chondrites, 4 carbonaceous chondrites, 2 enstatite chondrites, 3 ureilites, 3 eucrites, 1 acapulcoite, and 1 lunar meteorite. The median of 31 14 C terrestrial ages is 6.2 ka, significantly younger than the Oman population (19.5 ka, n = 128). A further assessment of terrestrial 14 C contamination is advised by a 11–15 ka 14 C terrestrial age of heavily weathered meteorite Khawr al Fazra 014, geology indicating a terrestrial age >100 ka. Find densities of 0.4–2.8 km −2 for Yabrin and the western Rub' al‐Khali are similar to 0.5 km −2 observed in Oman. Higher find densities of 135 km −2 (29 km −2 for masses >10 g) exist on small Pleistocene outcrops in blowouts in the south‐central Rub' al‐Khali: 21 unpaired meteorites (four >10 g) were found in 11 blowouts with a combined area of 0.14 km 2 . The Rub' al‐Khali meteorites show a relatively high degree of weathering (median W 3.6; 2.5 for Yabrin), low median mass (4.3/138 g), and a high H/L ratio (2.3/1.1). The high density of small meteorites is explained by prolonged sand protection and recent deflation. The high meteorite density and relatively high proportion of rare meteorite types render the Rub' al‐Khali blowouts an interesting target for future exploration.